Pharmacodynamics of converting enzyme inhibition: the cardiovascular, endocrine and autonomic effects of MK421 (enalapril) and MK521 - Millar, JA; Derkx, FH; McLean, K; Reid, JL (British journal of clinical pharmacology, 1982)
1 Two new orally active inhibitors of angiotensin converting enzyme MK421 (enalapril maleate) and its lysine analogue MK521 were given to nine salt-replete normal subjects in a randomised placebo-controlled study. 2 Supine and erect blood pressure and heart rate were measured before (0) and 1, 2, 4, 6, 8, 12 and 24 h after drug administration. Plasma converting enzyme, renin, renin substrate and noradrenaline levels were measured at 0, 2, 4, 6, 8, 12 and 24 h with measurement of plasma drug levels from 4 h in addition. Blood pressure and heart rate responses to Valsalva's manoeuvre, isometric exercise and the cold pressor test were measured at 0, 6 and 24 h and to dynamic exercise at 6 and 24 h. 3 Both MK421 and MK521 significantly inhibited plasma converting enzyme activity, but the inhibition was more prolonged after MK521. Plasma drug concentrations were correspondingly higher after MK521 at the later time intervals. Significant decreases in supine and erect blood pressure without a reflex increase in heart rate were observed after active drug treatment and plasma renin activity was increased. Renin substrate was decreased significantly after MK421. Maximum changes in blood pressure, renin and renin substrate occurred 4-6 h after drug ingestion, corresponding to peak plasma drug levels and maximal inhibition of converting enzyme. Hormonal changes were also more prolonged after MK521. Plasma noradrenaline was unchanged. No significant effects of active drug treatment on any test of autonomic function were seen. 4 MK421 and MK521 are potent inhibitors of converting enzyme which decrease blood pressure in normal subjects without reflex tachycardia. Pharmacodynamic effects on blood pressure and renin occur in parallel with plasma drug levels and converting enzyme inhibition. These studies suggest that the hypotensive effect of MK421 and MK521 is due to inhibition of the renin-angiotensin system secondary to converting enzyme inhibition. Absence of tachycardia during converting enzyme inhibition is not due to alterations in autonomic reflexes.